Correlation of Toluene Safe Duration (Hours/Day) and Glutathione Concentration, Malondialdehyde and Neurotoxic Symptoms in Osowilangun Shoe Home Industry Workers - Diah Pramesthi Ningrum1 , Abdul Rohim Tualeka2 , Juliana Jalaludin3 , Syamsiar S Russeng4 , Pudji Ra (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Exposure of toluene can cause a decrease in glutathione concentration, increase inmalondialdehyde and neurotoxic symptoms. The safe duration of toluene in hours/day for each person canvary. The purpose of this study is to determine the relationship between the safe duration of toluene (hours/day) with the concentration of glutathione, malondialdehyde and neurotoxic symptoms in Osowilangunshoe home industry workers.Methods: This research was observational with quantitative approach and cross-sectional design. Thesampling technique used was accidental sampling with 25 respondents. The variables studied were safetoluene duration (hours/day), glutathione concentration, malondialdehyde concentration, and neurotoxicsymptoms. Data were analyzed using Pearson and Phi correlation.Result: The average of safe duration was 1,489 hours/day, glutathione concentration was 58,349 µg/L,and malondialdehyde was 7,847 MU. As many as 11 out of 14 workers experienced neurotoxic symptoms.The relationship between safe duration (hours/day) with glutathione concentration (r=0.139) andmalondialdehyde (r=-0.146) was very weak. While, the relationship between safe duration (hours/day) andneurotoxic symptoms was weak (?=-0.223).Conclusion: The relationship between safe duration in hours/day with glutathione concentration andmalondialdehyde was very weak, while relationship with neurotoxic symptoms was weak.